Quantum synergistic film for solar cell and preparation method and application thereof
By applying a quantum synergistic film on the surface of solar cells, quantum dots are used to convert ultraviolet rays and block dust, the impact of ultraviolet rays and dust on solar cells is solved, and the photoelectric conversion efficiency and battery life are improved.
Patent Information
- Application Number
- CN202510238325.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The passivation layer structure of the existing solar cell modules is destroyed under ultraviolet irradiation, resulting in attenuation of photoelectric conversion efficiency, and dust accumulation reduces light transmittance, affecting battery life and output power.
A quantum synergistic film including quantum dots, polymer matrix, dustproofing agent, light stabilizer and functional additives is used to naturally convert ultraviolet rays through quantum dots to improve photoelectric conversion efficiency, and prevent dust adhesion through dustproofing agents.
It effectively reduces the impact of ultraviolet rays on solar cells, improves photoelectric conversion efficiency, extends the service life of the battery, and reduces maintenance costs.
Smart Images

Figure CN119708687A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a quantum efficiency enhancement film for solar cells and a preparation method and application thereof. Background Art
[0002] As an important conversion device for renewable energy, the photoelectric conversion efficiency and service life of solar cells are important indicators to measure their performance. However, there are several major problems in the actual use of solar cell modules in the prior art: First, ultraviolet rays can destroy the passivation layer structure on the surface of the cell, resulting in a gradual attenuation of the photoelectric conversion efficiency. For example, when n-type crystalline silicon solar cells are irradiated with ultraviolet light, a large amount of fixed charge will accumulate at the interface of the surface anti-reflection film SiN:H / Si, increasing the interface state density and destroying the passivation layer structure on the surface of the cell, thereby causing a large attenuation of the open circuit voltage and short circuit current. Secondly, the widespread presence of dust can not only lead to a decrease in transmittance and output power, but also affect the heat dissipation of the cell. Uneven heat dissipation forms a "hot spot" effect and shortens its service life. Existing data show that long-term dust accumulation can lead to a 6% to 12% reduction in power generation efficiency, and even a 20% to 25% reduction in arid environments; frequent cleaning is costly and there is also a risk of damaging the surface of the module. Finally, ultraviolet rays can also accelerate the aging process of component materials, including polymer materials such as EVA, silica gel, and backplane. The performance of these materials will change under long-term ultraviolet light irradiation, resulting in a decrease in the overall performance of the component. According to experimental data, the efficiency attenuation of the component materials of some n-type silicon solar cells can reach 3.6% after 35kWh / m² light irradiation. At low dose rates, when the electron irradiation dose reaches 200kGy, the maximum power of the battery drops by 40%, seriously reducing the battery life.
[0003] In the existing technology, although some researchers have studied covering the surface of the battery with a film to reduce the impact of ultraviolet rays and dust on the battery, it has caused the performance of the solar cell to decline. Therefore, how to ensure the performance of the solar cell while improving the battery life and dustproof function is still a technical challenge currently faced. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a quantum synergist film for solar cells and a preparation method and application thereof. In the present invention, when the quantum synergist film is applied to the surface of the battery, the film not only ensures the transmittance, but also can reduce the impact of ultraviolet rays on the solar cell; in addition, the film also has a dust-proof function.
[0005] The invention provides a quantum synergist film for solar cells. The synergist film comprises quantum dots, a polymer matrix, a dust repellent, a light stabilizer and a functional additive. The ratio of the quantum dots, the polymer matrix, the dust repellent, the light stabilizer and the functional additive is 1 part: (0.01 part to 5 parts): (0.5 part to 3 parts): (1 part to 5 parts): (0.5 part to 5 parts) by mass.
[0006] Furthermore, the quantum dots include one or more of cadmium-based quantum dots, sulfur-based quantum dots, perovskite quantum dots, carbon-based quantum dots, metal phosphide quantum dots, metal oxide quantum dots, metal nitride quantum dots, silicon-based quantum dots, and organic quantum dots.
[0007] Furthermore, the general formula of the cadmium-based quantum dots is CdW, wherein W is selected from S 2- 、Se 2- 、Te 2- One or more of .
[0008] Furthermore, the general formula of the sulfur-based quantum dots is M1 x S y , where M1 is selected as Zn 2+ 、Cd 2+ 、Ag + One or more of, x and y are determined by the method of balancing the chemical formula of sulfur-based quantum dots.
[0009] Furthermore, the general formula of the perovskite quantum dot is ABR3, wherein A is selected from one or more of formamidinium ion, methylamine ion, and cesium ion; B is selected from Pb 2+ Sn 2+ 、Eu 2+ , Cu 2+ 、Ni 2+ One or more of; R is selected from one or more of halogen ions.
[0010] Furthermore, the carbon-based quantum dots include carbon-based quantum dots composed of one or more elements selected from C, O, N and H.
[0011] Furthermore, the general formula of the metal phosphide quantum dot is M2 x1 P y1 , wherein M2 is selected from In 3+ , Ga 3+ 、Zn 2+ , Cu 2+ One or more of, x1 and y1 are determined by the method of balancing the chemical formula of metal phosphide quantum dots.
[0012] Furthermore, the general formula of the metal oxide quantum dot is M3 x2 O y2, wherein M3 is selected from Cu 2+ 、Zn 2+ , Fe 3+ , Ba 2+ 、Ti + , Li + , Mn 3+ , Mn 4+ One or more of, x2 and y2 are determined by the chemical formula balancing method of metal oxide quantum dots.
[0013] Furthermore, the general formula of the metal nitride quantum dot is M4 x3 N y3 , wherein M4 is selected from Ti 3+ 、Al 3+ , Ga 3+ , Fe 3+ , Fe 4+ One or more of, x3 and y3 are determined by the method of chemical formula balancing of metal nitride quantum dots.
[0014] Furthermore, the silicon-based quantum dots include one or more of intrinsic silicon-based quantum dots and doped silicon-based quantum dots.
[0015] Furthermore, the organic quantum dots include one or more of conjugated polymer quantum dots, dendrimer quantum dots, and organic small molecular weight quantum dots.
[0016] Furthermore, the size of the quantum dots is 3nm~30nm.
[0017] Furthermore, the main absorption band of the quantum dots is lower than 1000nm, and the emission wavelength is between 300nm and 1000nm.
[0018] Furthermore, the polymer matrix includes one or more of polyvinyl alcohol (PVA), polyethylene terephthalate (PET), polycarbonate (PC), polyethylene-polyvinyl acetate copolymer (EVA), ethylene and octene copolymer (POE), polyvinyl butyral (PVB), polyvinylidene fluoride (PVDF), polyvinyl acetate (PVAc), cellulose acetate (CA), polysulfone (PSU), aromatic polyamide (PPA), polyimide (PI), polystyrene (PS), polymethyl methacrylate (PMMA), thermoplastic polyolefin (TPO), and polyurethane (PU).
[0019] Furthermore, the dust suppressant includes one or more of nano silicon dioxide and nano aluminum oxide.
[0020] Furthermore, the light stabilizer includes one or more of a light shielding agent light stabilizer, a quencher light stabilizer, and a hindered amine light stabilizer.
[0021] Furthermore, the light-shielding agent-type light stabilizer includes one or more of titanium dioxide, zinc oxide and cerium oxide.
[0022] Furthermore, the quencher-type light stabilizer includes one or more of AM-101, N,N-di-n-butyldithiocarbamate nickel (NBC), zinc porphyrin and iron porphyrin.
[0023] Furthermore, the hindered amine light stabilizer includes one or more of Tinuvin 123, Chimassorb 944FD, Chimassorb 944FDL, Uvinul 4050H, light stabilizer 770, light stabilizer 944, light stabilizer 622, and light stabilizer 292.
[0024] Furthermore, the functional additives include one or more of organic small molecule passivators, high molecular polymer passivators, surfactants, high molecular dispersants, amino acids and their derivatives, organic phosphonic acid compounds, conductive polymer additives, and small molecule hole transport material additives.
[0025] Furthermore, the organic small molecule passivator includes one or more of ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), acetylacetone (acac), pyridine (Py) and aniline (An).
[0026] Furthermore, the high molecular polymer passivator includes one or more of polyvinyl pyrrolidone (PVP), polystyrene (PS), polyethylene glycol (PEG) and polyacrylic acid (PAA).
[0027] Furthermore, the surfactant includes one or more of sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), polyoxyethylene sorbitan monooleate (Tween-80), Triton X-100 (Triton X-100) and aureeth-7 (AEO-7).
[0028] Further, the polymer dispersant includes one or more of polycarboxylic acid sodium salt (PAA-Na), polystyrene-maleic anhydride copolymer (SMA), sodium polyacrylate (PAAS), polyvinyl butyral (PVB) and polyamide-amine (PAMAM) dendritic macromolecules. Furthermore, the amino acids and their derivatives include one or more of glycine (Gly), lysine (Lys), cysteine (Cys), glutamic acid (Glu) and phenylalanine (Phe).
[0029] Furthermore, the organic phosphonic acid compound includes one or more of aminotrimethylenephosphonic acid (ATMP), ethylenediaminetetramethylenephosphonic acid (EDTMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), hydroxyethylidene diphosphonic acid (HEDP) and hexamethylenediaminetetramethylenephosphonic acid (HDTMP).
[0030] Furthermore, the conductive polymer additive includes one or more of polyaniline (PANI), polythiophene (PTh), polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(p-phenylenevinylene) (PPV).
[0031] Further, the small molecule hole transport material additive includes one or more of N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), N,N'-di(1-naphthyl)-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (α-NPD), spiro-bifluorene-9,9'-bis(9-phenyl-9H-carbazole) (Spiro-OMeTAD), 4-(diphenylamino)benzaldehyde (DPAB) and tris(4-bromophenyl)amine (TBPA).
[0032] The present invention also provides a method for preparing the quantum efficiency enhancement film for solar cells, which is selected from Scheme I to Scheme II: Option I: S1: heating the polymer matrix and coating the polymer matrix with quantum dots; S2: mixing the product obtained in S1 with a dust suppressant, a light stabilizer and a functional additive to form a quantum efficiency enhancement film for solar cells; Option II: Step 1: heating the polymer matrix and coating the polymer matrix with quantum dots; Step 2: Mixing the light stabilizer obtained in S1 and the functional additive; Step 3: Finally, apply a dust repellent to form a quantum efficiency enhancement film for solar cells.
[0033] Furthermore, the heating temperature is 95°C-105°C, and the heating time is 9min-11min.
[0034] Furthermore, by mass, the ratio of the quantum dots, polymer matrix, dust suppressant, light stabilizer and functional additive is 1 part: (0.01 part to 5 parts): (0.5 part to 3 parts): (1 part to 5 parts): (0.5 part to 5 parts).
[0035] Furthermore, the quantum dots include one or more of cadmium-based quantum dots, sulfur-based quantum dots, perovskite quantum dots, carbon-based quantum dots, metal phosphide quantum dots, metal oxide quantum dots, metal nitride quantum dots, silicon-based quantum dots, and organic quantum dots.
[0036] Furthermore, the general formula of the cadmium-based quantum dots is CdW, wherein W is selected from S 2- 、Se 2- 、Te 2- One or more of .
[0037] Furthermore, the general formula of the sulfur-based quantum dots is M1 x S y , where M1 is selected as Zn 2+ 、Cd 2+ 、Ag + One or more of, x and y are determined by the method of balancing the chemical formula of sulfur-based quantum dots.
[0038] Furthermore, the general formula of the perovskite quantum dot is ABR3, wherein A is selected from one or more of formamidinium ion, methylamine ion, and cesium ion; B is selected from Pb 2+ Sn 2+ 、Eu 2+ , Cu 2+ 、Ni 2+ One or more of; R is selected from one or more of halogen ions.
[0039] Furthermore, the carbon-based quantum dots include carbon-based quantum dots composed of one or more elements selected from C, O, N and H.
[0040] Furthermore, the general formula of the metal phosphide quantum dot is M2 x1 P y1 , wherein M2 is selected from In 3+ , Ga 3+ 、Zn 2+ , Cu 2+ One or more of, x1 and y1 are determined by the method of balancing the chemical formula of metal phosphide quantum dots.
[0041] Furthermore, the general formula of the metal oxide quantum dot is M3 x2 O y2 , wherein M3 is selected from Cu 2+ 、Zn 2+ , Fe 3+ , Ba 2+ 、Ti + , Li + , Mn 3+ , Mn 4+One or more of, x2 and y2 are determined by the chemical formula balancing method of metal oxide quantum dots.
[0042] Furthermore, the general formula of the metal nitride quantum dot is M4 x3 N y3 , wherein M4 is selected from Ti 3+ 、Al 3+ , Ga 3+ , Fe 3+ , Fe 4+ One or more of, x3 and y3 are determined by the method of chemical formula balancing of metal nitride quantum dots.
[0043] Furthermore, the silicon-based quantum dots include one or more of intrinsic silicon-based quantum dots and doped silicon-based quantum dots.
[0044] Furthermore, the organic quantum dots include one or more of conjugated polymer quantum dots, dendrimer quantum dots, and organic small molecular weight quantum dots.
[0045] Furthermore, the size of the quantum dots is 3nm~30nm.
[0046] Furthermore, the polymer matrix includes one or more of polyvinyl alcohol (PVA), polyethylene terephthalate (PET), polycarbonate (PC), polyethylene-polyvinyl acetate copolymer (EVA), ethylene and octene copolymer (POE), polyvinyl butyral (PVB), polyvinylidene fluoride (PVDF), polyvinyl acetate (PVAc), cellulose acetate (CA), polysulfone (PSU), aromatic polyamide (PPA), polyimide (PI), polystyrene (PS), polymethyl methacrylate (PMMA), thermoplastic polyolefin (TPO), and polyurethane (PU).
[0047] Furthermore, the dust suppressant includes one or more of nano silicon dioxide and nano aluminum oxide.
[0048] Furthermore, the light stabilizer includes one or more of a light shielding agent light stabilizer, a quencher light stabilizer, and a hindered amine light stabilizer.
[0049] Furthermore, the light-shielding agent-type light stabilizer includes one or more of titanium dioxide, zinc oxide and cerium oxide.
[0050] Furthermore, the quencher-type light stabilizer includes one or more of AM-101, NBC, zinc porphyrin and iron porphyrin.
[0051] Furthermore, the hindered amine light stabilizer includes one or more of Tinuvin 123, Chimassorb 944FD, Chimassorb 944FDL, Uvinul 4050H, light stabilizer 770, light stabilizer 944, light stabilizer 622, and light stabilizer 292.
[0052] Furthermore, the functional additives include one or more of organic small molecule passivators, high molecular polymer passivators, surfactants, high molecular dispersants, amino acids and their derivatives, organic phosphonic acid compounds, conductive polymer additives, and small molecule hole transport material additives.
[0053] Furthermore, the organic small molecule passivator includes one or more of ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), acetylacetone (acac), pyridine (Py) and aniline (An).
[0054] Furthermore, the high molecular polymer passivator includes one or more of polyvinyl pyrrolidone (PVP), polystyrene (PS), polyethylene glycol (PEG) and polyacrylic acid (PAA).
[0055] Furthermore, the surfactant includes one or more of sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), polyoxyethylene sorbitan monooleate (Tween-80), Triton X-100 (Triton X-100) and aureeth-7 (AEO-7).
[0056] Further, the polymer dispersant includes one or more of polycarboxylic acid sodium salt (PAA-Na), polystyrene-maleic anhydride copolymer (SMA), sodium polyacrylate (PAAS), polyvinyl butyral (PVB) and polyamide-amine (PAMAM) dendritic macromolecules. Furthermore, the amino acids and their derivatives include one or more of glycine (Gly), lysine (Lys), cysteine (Cys), glutamic acid (Glu) and phenylalanine (Phe).
[0057] Furthermore, the organic phosphonic acid compound includes one or more of aminotrimethylenephosphonic acid (ATMP), ethylenediaminetetramethylenephosphonic acid (EDTMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), hydroxyethylidene diphosphonic acid (HEDP) and hexamethylenediaminetetramethylenephosphonic acid (HDTMP).
[0058] Furthermore, the conductive polymer additive includes one or more of polyaniline (PANI), polythiophene (PTh), polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(p-phenylenevinylene) (PPV).
[0059] Furthermore, the small molecule hole transport material additive includes one or more of N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), N,N'-di(1-naphthyl)-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (α-NPD), spiro-bifluorene-9,9'-bis(9-phenyl-9H-carbazole) (Spiro-OMeTAD), 4-(diphenylamino)benzaldehyde (DPAB) and tris(4-bromophenyl)amine (TBPA).
[0060] The present invention also provides application of the quantum efficiency enhancement film for solar cells in solar cells.
[0061] Furthermore, the solar cell quantum efficiency enhancement film is arranged on the surface of the solar cell.
[0062] Furthermore, the solar cell includes a silicon-based solar cell, a thin-film solar cell, a dye-sensitized solar cell or a perovskite solar cell.
[0063] The embodiments of the present invention have the following technical effects: 1. In the present invention, quantum enhancement film is used in solar cells. The basic principle is to use a dustproof agent with anti-static and dustproof effects and design the surface structure of the enhancement film to reduce the scattering of sunlight by dust. At the same time, the special quantum dots in the film naturally convert ultraviolet rays and short-wave light into green light with high quantum efficiency, thereby improving the photoelectric conversion efficiency and eliminating the light corrosion of ultraviolet rays. At the same time, it has a dustproof function, effectively blocking dust and other pollutants from adhering to the surface of solar cells, extending the service life of solar cells, and reducing maintenance costs.
[0064] 2. The quantum dot enhancement film for solar cells obtained in the present invention not only has a quantum dot enhancement function, which can improve the photoelectric conversion efficiency of solar cells, but also has a dustproof function, effectively extending the service life of solar cells. By precisely controlling the synthesis and preparation process, the uniform distribution and high stability of quantum dots in the film are achieved, providing a new solution for solar cells to enhance efficiency and prevent dust. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0066] Figure 1 This is a PL test diagram of the CdSe quantum enhancement film in the present invention; Figure 2 This is a PL test diagram of the ZnS quantum enhancement film in the present invention; Figure 3 TEM image of CsPbBr3 perovskite quantum dots in the present invention; Figure 4 This is a PL test diagram of the CsPbBr3 quantum enhancement film in the present invention; Figure 5 This is a PL test diagram of the CsPbI3 quantum enhancement film in the present invention; Figure 6 In the present invention, CsPbBr 0.5 Cl 2.5 PL test diagram of quantum efficiency film; Figure 7 is the transmittance of the CsPbBr3 quantum enhancement film in the present invention; Figure 8 It is the photoelectric conversion efficiency of the CsPbBr3 quantum dot enhancement film in the present invention. DETAILED DESCRIPTION
[0067] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0068] In a first aspect, some embodiments of the present invention provide a quantum enhancement film for solar cells, the enhancement film comprising quantum dots, a polymer matrix, a dust repellent, a light stabilizer and a functional additive, and the ratio of the quantum dots, the polymer matrix, the dust repellent, the light stabilizer and the functional additive is 1 part: (0.01 part to 5 parts): (0.5 part to 3 parts): (1 part to 5 parts): (0.5 part to 5 parts) by mass.
[0069] In some embodiments, the quantum dots include one or more of cadmium-based quantum dots, sulfur-based quantum dots, perovskite quantum dots, carbon-based quantum dots, metal phosphide quantum dots, metal oxide quantum dots, metal nitride quantum dots, silicon-based quantum dots, and organic quantum dots.
[0070] In some embodiments, the general formula of the cadmium-based quantum dots is CdW, wherein W is selected from S 2- 、Se 2- 、Te 2- One or more of .
[0071] In some embodiments, the general formula of the sulfur-based quantum dots is M1 x S y , where M1 is selected as Zn 2+ 、Cd 2+ 、Ag + One or more of, x and y are determined by the method of balancing the chemical formula of sulfur-based quantum dots.
[0072] In some embodiments, the general formula of the perovskite quantum dot is ABR3, wherein A is selected from one or more of formamidinium ion, methylamine ion, and cesium ion; B is selected from Pb 2+ Sn 2+ 、Eu 2+ , Cu 2+ 、Ni 2+ One or more of; R is selected from one or more of halogen ions.
[0073] In some embodiments, the carbon-based quantum dots include carbon-based quantum dots composed of one or more elements selected from C, O, N and H.
[0074] In some embodiments, the general formula of the metal phosphide quantum dot is M2 x1 P y1 , wherein M2 is selected from In 3+ , Ga 3+ 、Zn 2+ , Cu 2+ One or more of, x1 and y1 are determined by the method of balancing the chemical formula of metal phosphide quantum dots.
[0075] In some embodiments, the general formula of the metal oxide quantum dot is M3 x2 O y2 , wherein M3 is selected from Cu 2+ 、Zn 2+ , Fe 3+ , Ba 2+ 、Ti + , Li + , Mn 3+ , Mn4+ One or more of, x2 and y2 are determined by the chemical formula balancing method of metal oxide quantum dots.
[0076] In some embodiments, the general formula of the metal nitride quantum dot is M4 x3 N y3 , wherein M4 is selected from Ti 3+ 、Al 3+ , Ga 3+ , Fe 3+ , Fe 4+ One or more of, x3 and y3 are determined by the method of chemical formula balancing of metal nitride quantum dots.
[0077] In some embodiments, the silicon-based quantum dots include one or more of intrinsic silicon-based quantum dots and doped silicon-based quantum dots.
[0078] In some embodiments, the organic quantum dots include one or more of conjugated polymer quantum dots, dendrimer quantum dots, and organic small molecular weight quantum dots.
[0079] In some embodiments, the size of the quantum dots is 3 nm to 30 nm.
[0080] The quantum dots of the present invention are nanometer-level in size, and the energy gap of smaller-sized quantum dots is larger, so they can absorb more energy and improve the photoelectric conversion efficiency; quantum dots can produce a stronger light scattering effect in the solar cell film, making the propagation path of light in the film longer, increasing the probability of interaction between photons and quantum dots, thereby improving the light absorption efficiency.
[0081] In the present invention, the preparation of quantum dots can be obtained by selecting a preparation method according to actual conditions by a person skilled in the art. The preparation methods include hot injection method, sol-gel method, and ligand-assisted reprecipitation method. Specifically, the main absorption band of the quantum dots of the present invention is below 1000nm, the emission wavelength is within the range of 300nm to 1000nm, the fluorescence yield of the quantum dots is greater than 70%, and the half-peak width is less than 50nm.
[0082] In some embodiments, the polymer matrix includes one or more of polyvinyl alcohol (PVA), polyethylene terephthalate (PET), polycarbonate (PC), polyethylene-polyvinyl acetate copolymer (EVA), ethylene and octene copolymer (POE), polyvinyl butyral (PVB), polyvinylidene fluoride (PVDF), polyvinyl acetate (PVAc), cellulose acetate (CA), polysulfone (PSU), aromatic polyamide (PPA), polyimide (PI), polystyrene (PS), polymethyl methacrylate (PMMA), thermoplastic polyolefin (TPO), and polyurethane (PU).
[0083] In some embodiments, the dust suppressant includes one or more of nano-silicon dioxide and nano-aluminum oxide.
[0084] In some embodiments, the light stabilizer includes one or more of a light shielding agent light stabilizer, a quencher light stabilizer, and a hindered amine light stabilizer.
[0085] In some embodiments, the light-shielding agent-type light stabilizer includes titanium dioxide, zinc oxide, cerium oxide or other suitable light-shielding agent-type light stabilizers.
[0086] In some embodiments, the quencher photostabilizer includes AM-101, NBC, zinc porphyrin, iron porphyrin or other suitable quencher photostabilizers.
[0087] In some embodiments, the hindered amine light stabilizer includes Tinuvin 123, Chimassorb 944FD, Chimassorb 944FDL, Uvinul 4050H, light stabilizer-770, light stabilizer-944, light stabilizer-622, light stabilizer 292 or other suitable hindered amine light stabilizers.
[0088] In some embodiments, the functional additives include one or more of organic small molecule passivators, high molecular polymer passivators, surfactants, high molecular dispersants, amino acids and their derivatives, organic phosphonic acid compounds, conductive polymer additives, and small molecule hole transport material additives.
[0089] In some embodiments, the organic small molecule passivator includes ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), acetylacetone (acac), pyridine (Py), aniline (An) or other suitable organic small molecule passivators.
[0090] In some embodiments, the polymer passivator includes polyvinyl pyrrolidone (PVP), polystyrene (PS), polyethylene glycol (PEG), polyacrylic acid (PAA) or other suitable polymer passivators.
[0091] In some embodiments, the surfactant includes sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), polyoxyethylene sorbitan monooleate (Tween-80), Triton X-100 (Triton X-100), laureth-7 (AEO-7) or other suitable surfactants.
[0092] In some embodiments, the polymer dispersant includes polycarboxylic acid sodium salt (PAA-Na), polystyrene-maleic anhydride copolymer (SMA), sodium polyacrylate (PAAS), polyvinyl butyral (PVB), polyamide-amine (PAMAM) dendrimers or other suitable polymer dispersants.
[0093] In some embodiments, the amino acids and their derivatives include glycine (Gly), lysine (Lys), cysteine (Cys), glutamic acid (Glu), phenylalanine (Phe) or other suitable amino acids and their derivatives.
[0094] In some embodiments, the organic phosphonic acid compound includes aminotrimethylenephosphonic acid (ATMP), ethylenediaminetetramethylenephosphonic acid (EDTMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), hydroxyethylidene diphosphonic acid (HEDP), hexamethylenediaminetetramethylenephosphonic acid (HDTMP) or other suitable organic phosphonic acid compounds.
[0095] In some embodiments, the conductive polymer additive includes polyaniline (PANI), polythiophene (PTh), polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylenevinylene) (PPV), or other suitable conductive polymer additives.
[0096] In some embodiments, the small molecule hole transport material additive includes one or more of N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), N,N'-di(1-naphthyl)-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (α-NPD), spiro-bifluorene-9,9'-bis(9-phenyl-9H-carbazole) (Spiro-OMeTAD), 4-(diphenylamino)benzaldehyde (DPAB) and tris(4-bromophenyl)amine (TBPA).
[0097] In a second aspect, some embodiments of the present invention further provide a method for preparing the quantum efficiency enhancement film for solar cells, wherein one of Scheme I and Scheme II is selected: Option I: S1: heating the polymer matrix and coating the polymer matrix with quantum dots; S2: mixing the product obtained in S1 with a dust suppressant, a light stabilizer and a functional additive to form a quantum efficiency enhancement film for solar cells; Option II: Step 1: heating the polymer matrix and coating the polymer matrix with quantum dots; Step 2: Mixing the light stabilizer obtained in S1 and the functional additive; Step 3: Finally, apply a dust repellent to form a quantum efficiency enhancement film for solar cells.
[0098] In the present invention, those skilled in the art can select a method for forming a film according to actual conditions. The method for forming a film from the mixed slurry includes spin coating, casting, dip coating, spray coating, hot pressing, extrusion, interfacial polymerization, in-situ polymerization, and demulsification-induced rapid solidification.
[0099] In some embodiments, the heating temperature is 95° C. to 105° C., and the heating time is 9 min to 11 min.
[0100] In some embodiments, the ratio of the quantum dots, polymer matrix, dust repellent, light stabilizer and functional additives is 1 part: (0.01 part to 5 parts): (0.5 part to 3 parts): (1 part to 5 parts): (0.5 part to 5 parts) by mass.
[0101] In some embodiments, the quantum dots include one or more of cadmium-based quantum dots, sulfur-based quantum dots, perovskite quantum dots, carbon-based quantum dots, metal phosphide quantum dots, metal oxide quantum dots, metal nitride quantum dots, silicon-based quantum dots, and organic quantum dots.
[0102] In some embodiments, the general formula of the cadmium-based quantum dots is CdW, wherein W is selected from S 2- 、Se 2- 、Te 2- One or more of .
[0103] In some embodiments, the general formula of the sulfur-based quantum dots is M1 x S y , where M1 is selected as Zn 2+ 、Cd 2+ 、Ag + One or more of, x and y are determined by the method of balancing the chemical formula of sulfur-based quantum dots.
[0104] In some embodiments, the general formula of the perovskite quantum dot is ABR3, wherein A is selected from one or more of formamidinium ion, methylamine ion, and cesium ion; B is selected from Pb 2+ Sn 2+ 、Eu 2+ , Cu 2+ 、Ni 2+ One or more of; R is selected from one or more of halogen ions.
[0105] In some embodiments, the carbon-based quantum dots include carbon-based quantum dots composed of one or more elements selected from C, O, N and H.
[0106] In some embodiments, the general formula of the metal phosphide quantum dot is M2 x1 P y1 , wherein M2 is selected from In 3+ , Ga 3+ 、Zn 2+ , Cu 2+ One or more of, x1 and y1 are determined by the method of balancing the chemical formula of metal phosphide quantum dots.
[0107] In some embodiments, the general formula of the metal oxide quantum dot is M3 x2 O y2 , wherein M3 is selected from Cu 2+ 、Zn 2+ , Fe 3+ , Ba 2+ 、Ti + , Li + , Mn 3+ , Mn 4+ One or more of, x2 and y2 are determined by the chemical formula balancing method of metal oxide quantum dots.
[0108] In some embodiments, the general formula of the metal nitride quantum dot is M4 x3 N y3 , wherein M4 is selected from Ti 3+ 、Al 3+ , Ga 3+ , Fe 3+ , Fe 4+ One or more of, x3 and y3 are determined by the method of chemical formula balancing of metal nitride quantum dots.
[0109] In some embodiments, the silicon-based quantum dots include one or more of intrinsic silicon-based quantum dots and doped silicon-based quantum dots.
[0110] In some embodiments, the organic quantum dots include one or more of conjugated polymer quantum dots, dendrimer quantum dots, and organic small molecular weight quantum dots.
[0111] In some embodiments, the size of the quantum dots is 3-30 nm.
[0112] In some embodiments, the polymer matrix includes one or more of polyvinyl alcohol (PVA), polyethylene terephthalate (PET), polycarbonate (PC), polyethylene-polyvinyl acetate copolymer (EVA), ethylene and octene copolymer (POE), polyvinyl butyral (PVB), polyvinylidene fluoride (PVDF), polyvinyl acetate (PVAc), cellulose acetate (CA), polysulfone (PSU), aromatic polyamide (PPA), polyimide (PI), polystyrene (PS), polymethyl methacrylate (PMMA), thermoplastic polyolefin (TPO), and polyurethane (PU).
[0113] In some embodiments, the dust suppressant includes one or more of nano-silicon dioxide and nano-aluminum oxide.
[0114] In some embodiments, the light stabilizer includes one or more of a light shielding agent light stabilizer, a quencher light stabilizer, and a hindered amine light stabilizer.
[0115] In some embodiments, the light-shielding agent-type light stabilizer includes titanium dioxide, zinc oxide, cerium oxide or other suitable light-shielding agent-type light stabilizers.
[0116] In some embodiments, the quencher photostabilizer includes AM-101, NBC, zinc porphyrin, iron porphyrin or other suitable quencher photostabilizers.
[0117] In some embodiments, the hindered amine light stabilizer includes Tinuvin 123, Chimassorb 944FD, Chimassorb 944FDL, Uvinul 4050H, light stabilizer-770, light stabilizer-944, light stabilizer-622, light stabilizer 292 or other suitable hindered amine light stabilizers.
[0118] In some embodiments, the functional additives include one or more of organic small molecule passivators, high molecular polymer passivators, surfactants, high molecular dispersants, amino acids and their derivatives, organic phosphonic acid compounds, conductive polymer additives, and small molecule hole transport material additives.
[0119] In some embodiments, the organic small molecule passivator includes ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), acetylacetone (acac), pyridine (Py), aniline (An) or other suitable organic small molecule passivators.
[0120] In some embodiments, the polymer passivator includes polyvinyl pyrrolidone (PVP), polystyrene (PS), polyethylene glycol (PEG), polyacrylic acid (PAA) or other suitable polymer passivators.
[0121] In some embodiments, the surfactant includes sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), polyoxyethylene sorbitan monooleate (Tween-80), Triton X-100 (Triton X-100), laureth-7 (AEO-7) or other suitable surfactants.
[0122] In some embodiments, the polymer dispersant includes polycarboxylic acid sodium salt (PAA-Na), polystyrene-maleic anhydride copolymer (SMA), sodium polyacrylate (PAAS), polyvinyl butyral (PVB), polyamide-amine (PAMAM) dendrimers or other suitable polymer dispersants.
[0123] In some embodiments, the amino acids and their derivatives include glycine (Gly), lysine (Lys), cysteine (Cys), glutamic acid (Glu), phenylalanine (Phe) or other suitable amino acids and their derivatives.
[0124] In some embodiments, the organic phosphonic acid compound includes aminotrimethylenephosphonic acid (ATMP), ethylenediaminetetramethylenephosphonic acid (EDTMP), 2-phosphonobutane-1,2,4-tricarboxylic acid (PBTCA), hydroxyethylidene diphosphonic acid (HEDP), hexamethylenediaminetetramethylenephosphonic acid (HDTMP) or other suitable organic phosphonic acid compounds.
[0125] In some embodiments, the conductive polymer additive includes polyaniline (PANI), polythiophene (PTh), polypyrrole (PPy), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylenevinylene) (PPV), or other suitable conductive polymer additives.
[0126] In some embodiments, the small molecule hole transport material additive includes one or more of N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), N,N'-di(1-naphthyl)-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (α-NPD), spiro-bifluorene-9,9'-bis(9-phenyl-9H-carbazole) (Spiro-OMeTAD), 4-(diphenylamino)benzaldehyde (DPAB) and tris(4-bromophenyl)amine (TBPA).
[0127] In a third aspect, some embodiments of the present invention also provide applications of the quantum efficiency enhancement film for solar cells in solar cells.
[0128] In some embodiments, the solar cell quantum efficiency enhancement film is disposed on the surface of the solar cell.
[0129] In some embodiments, the solar cell includes a silicon-based solar cell, a thin-film solar cell, a dye-sensitized solar cell or a perovskite solar cell.
[0130] The following is described in detail with reference to specific embodiments and comparative examples: Embodiment 1:
[0131] Step (1): Mix 2.5 mmol of selenium powder, 1.0 mL of trioctylphosphine sulfide (TOP) and 10.0 mL of 1-octadecene (ODE), evacuate the reaction bottle for 80 min, then increase the temperature and heat to 250 °C under nitrogen protection for 2 h to obtain a selenium precursor for use.
[0132] Step (2): 3 mmol of CdO, 5.5 mL of oleic acid (OA) and 50 mL of ODE were mixed, vacuumed and heated to 180°C. After all the solids were dissolved, the mixture was cooled to room temperature, 3.5 mL of OA and 3.5 mL of oleylamine (OAm) were added, and the temperature was then raised to 240°C. After reaching the temperature, the selenium precursor (3 mL) in step (1) heated to 250°C was immediately injected. After reacting for 30 s, the heating jacket was removed, and the mixture was cooled to room temperature using an ice water bath. The mixture was centrifuged and purified using methyl acetate at a speed of 6500 rpm for 10 min to obtain CdSe quantum dots, which were then stored in n-hexane for later use. In the present invention, CdSe quantum dots can also be obtained commercially.
[0133] Step (3): 1.5 mg of the polymer matrix ethylene-vinyl acetate copolymer (EVA) was heated at 100°C for 10 min, and 0.5 mL of the CdSe quantum dots (10 mg / mL) obtained in step (2) was added.
[0134] Step (4): Then add 10 mg of the functional additive polyvinyl pyrrolidone (PVP), and after defoaming, add 7.5 mg of silicon dioxide (SiO2) and 15 mg of light stabilizer TiO2, mix well and let stand to defoam, then pour the mixed solvent on the photovoltaic panel and apply it by scraping. After drying, the resulting film is the self-cleaning quantum efficiency enhancement film for solar cells.
[0135] Step (5): Test the quantum efficiency enhancement film.
[0136] Embodiment 2:
[0137] Step (1): Mix 2.5 mmol sulfur powder, 1.0 mL TOP and 10.0 mL ODE, evacuate the reaction bottle for 80 min, then increase the temperature and heat to 200 °C under nitrogen protection for 2 h to obtain a sulfur precursor for use.
[0138] Step (2): 3 mmol of zinc acetate (Zn(CH3COO)2) and 5.5 mL of OA and 50 mL of ODE were mixed, vacuumed and heated to 150°C. After the solid was completely dissolved, it was cooled to room temperature, 3.5 mL of OA and 3.5 mL of OAm were added, and then the temperature was raised to 180°C. After reaching the temperature, the selenium precursor (3 mL) in step (1) heated to 200°C was immediately injected. After reacting for 30 s, the heating jacket was removed, and the mixture was cooled to room temperature using an ice water bath. It was centrifuged and purified with methyl acetate at a speed of 6500 rpm for 10 min to obtain ZnS quantum dots, which were then stored in n-hexane for later use. In the present invention, ZnS quantum dots can also be obtained commercially.
[0139] Step (3): 1.5 mg of the polymer matrix ethylene-vinyl acetate copolymer (EVA) was heated at 100°C for 10 min, and 0.5 mL of the ZnS quantum dots (10 mg / mL) obtained in step (2) was added.
[0140] Step (4): Then add 10 mg of the functional additive polyvinyl pyrrolidone (PVP), and after defoaming, add 7.5 mg of silicon dioxide (SiO2) and 15 mg of light stabilizer TiO2, mix well and let stand to defoam, then pour the mixed solvent on the photovoltaic panel and apply it by scraping. After drying, the resulting film is the self-cleaning quantum efficiency enhancement film for solar cells.
[0141] Step (5): Test the quantum efficiency enhancement film.
[0142] Embodiment 3:
[0143] Step (1): After mixing 2.5 mmol of cesium carbonate (Cs2CO3), 2 mL of OA and 30 mL of ODE, the reaction bottle was evacuated for 80 min, and then the temperature was increased and heated to 150°C under nitrogen protection and maintained for 2 h, and then a clear cesium oleate solution was obtained.
[0144] Step (2): 35 mL of ODE and 2 mmol of lead bromide (PbBr2) were mixed, vacuum heated to 150°C, and then 3 mL of OA and 3 mL of OAm were added under nitrogen protection. The temperature was then raised to 180°C. After reaching the temperature, cesium oleate (3 mL) heated to 150°C in step (1) was immediately injected, and then quickly cooled to room temperature with an ice water bath. The mixture was centrifuged and purified with methyl acetate at a speed of 8000 rpm for 5 min to obtain CsPbBr3 perovskite quantum dots, which were then stored in n-hexane for later use.
[0145] Step (3): 1.5 mg of polymer matrix ethylene-vinyl acetate copolymer (EVA) was heated at 100°C for 10 min, and 0.5 mL of perovskite quantum dots (10 mg / mL) obtained in step (2) was added.
[0146] Step (4): Then add 10 mg of the functional additive polyvinyl pyrrolidone (PVP), and after defoaming, add 7.5 mg of silicon dioxide (SiO2) and 15 mg of light stabilizer TiO2, mix well and let stand to defoam, then pour the mixed solvent on the photovoltaic panel and apply it by scraping. After drying, the resulting film is the self-cleaning quantum efficiency enhancement film for solar cells.
[0147] Step (5): Test the quantum efficiency enhancement film.
[0148] Embodiment 4:
[0149] The difference between Example 4 and Example 3 is that the prepared perovskite quantum dots are CsPbI3, so lead iodide is used instead of lead bromide when preparing the perovskite quantum dots, and the rest are the same as Example 3.
[0150] Embodiment 5:
[0151] The difference between Example 5 and Example 3 is that the prepared perovskite quantum dots are CsPbBr 0.5 Cl 2.5 Therefore, lead chloride and lead bromide are used in preparing perovskite quantum dots, and the rest are the same as in Example 3.
[0152] Comparative Example 1: The difference between Comparative Example 1 and Example 3 is that no perovskite quantum dots are added, and the rest is the same as Example 3.
[0153] The films obtained from the embodiments and comparative examples were compared and tested: Test method: Transmission Electron Microscope (TEM): This experiment uses JEOL's JEM-2800 TEM to observe microstructures at the micrometer and nanometer scales. Before scanning, the quantum point solution to be measured needs to be dispersed on a micro-grid copper mesh covered with an ultra-thin carbon film and observed after it is fully dried.
[0154] Steady-state Photoluminescence Spectra (PL): When the sample is excited by light, electrons jump from the valence band to the conduction band and leave holes in the valence band. The electrons in the conduction band and the holes in the valence band relax to the bottom of the conduction band or the top of the valence band, and then emit photons through radiation recombination to return to the ground state, thus forming a spectrum of light with different wavelengths and intensities. The steady-state photoluminescence spectrometer used in this experiment is Edinburgh's FS5, with an excitation wavelength of 450 nm.
[0155] UV-Vis Absorption Spectrum: Prepare the quantum film on the substrate, ensure the uniformity and integrity of the film, put it into the sample cell of the UV-visible spectrophotometer, set the wavelength range to 200~800nm, and measure the absorbance or transmittance at different wavelengths. According to the formula T=10 -A (Where T is transmittance and A is absorbance) Calculate the transmittance at each wavelength. The UV spectrophotometer used in this experiment is Cary 100 from Varian.
[0156] Fluorescence quantum yield (PLQY): Fluorescence quantum yield refers to the ratio of the fluorescence intensity of the material under certain excitation light to the intensity of the absorbed excitation light, which is used to characterize the efficiency of the sample in emitting fluorescence. The steady-state photoluminescence spectrometer used in this experiment is Edinburgh's FS5, with an excitation wavelength of 450 nm.
[0157] Photoelectric conversion efficiency: The CsPbBr3 quantum dot film was prepared into a complete solar cell structure, and the open circuit voltage (V oc )、Short-circuit current(I sc ), fill factor (FF) and other key parameters, and then calculate the photoelectric conversion efficiency. Under standard test conditions, that is, the light intensity is 1000W / m 2 , AM1.5 spectrum distribution, the calculation formula for photoelectric conversion efficiency is η=V oc ×I sc ×FF / P in×100%, where P in Incident light power density.
[0158] Results and analysis: like Figure 1 This is a PL test image of the CdSe quantum enhancement film prepared in Example 1, with an emission position at 549 nm and a FWHM of 35 nm.
[0159] like Figure 2 This is a PL test image of the ZnS quantum efficiency enhancement film prepared in Example 2, with an emission position at 525 nm and a FWHM of 25 nm.
[0160] like Figure 3 This is a TEM image of the CsPbBr3 quantum dots prepared in Example 3, where the morphology of the CsPbBr3 quantum dots with uniform and monodisperse cubic shapes can be observed; like Figure 4 This is a PL test image of the CsPbBr3 quantum efficiency enhancement film prepared in Example 3, with an emission position at 513.5 nm and a FWHM of 29.4 nm.
[0161] like Figure 5 This is a PL test image of the CsPbI3 quantum efficiency enhancement film prepared in Example 4, with an emission position at 684.4 nm and a FWHM of 43.5 nm.
[0162] like Figure 6 The CsPbBr prepared in Example 5 0.5 Cl 2.5 The PL test pattern of the quantum efficiency enhancement film shows that its emission position is at 409.4 nm and its FWHM is 18.63 nm.
[0163] like Figure 7 This is the transmittance diagram of the CsPbBr3 quantum enhancement film prepared in Example 3, and its transmittance in the visible light part is >97.67%.
[0164] like Figure 8 As shown, the CsPbBr3 quantum dot enhancement film prepared in Example 3 is applied to the surface of a solar cell compared to the film obtained in Comparative Example 1. The photoelectric conversion efficiency of the solar cell in Example 3 is increased by 7%, and the quantum efficiency of the CsPbBr3 quantum dot enhancement film is 82.79%.
[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A quantum efficiency enhancement film for solar cells, characterized in that: The synergistic film includes quantum dots, a polymer matrix, a dust repellent, a light stabilizer and a functional additive. By mass, the ratio of the quantum dots, the polymer matrix, the dust repellent, the light stabilizer and the functional additive is 1 part: (0.01 part to 5 parts): (0.5 part to 3 parts): (1 part to 5 parts): (0.5 part to 5 parts).
2. The quantum efficiency enhancement film for solar cells according to claim 1, characterized in that: The quantum dots include one or more of cadmium-based quantum dots, sulfur-based quantum dots, perovskite quantum dots, carbon-based quantum dots, metal phosphide quantum dots, metal oxide quantum dots, metal nitride quantum dots, silicon-based quantum dots, and organic quantum dots.
3. The quantum efficiency enhancement film for solar cells according to claim 2, characterized in that: The general formula of the cadmium-based quantum dots is CdW, wherein W is selected from S 2- 、Se 2- 、Te 2- One or more of; The general formula of the sulfur-based quantum dots is M1 x S y , where M1 is selected as Zn 2+ 、Cd 2+ 、Ag + One or more of, x and y are determined by the method of balancing the chemical formula of sulfur-based quantum dots; The general formula of the perovskite quantum dot is ABR3, wherein A is selected from one or more of formamidinium ion, methylamine ion, and cesium ion; B is selected from Pb 2+ Sn 2+ 、Eu 2+ , Cu 2+ 、Ni 2+ One or more of; R is selected from one or more of halogen ions; The carbon-based quantum dots include carbon-based quantum dots composed of one or more elements selected from C, O, N and H; The general formula of the metal phosphide quantum dot is M2 x1 P y1 , wherein M2 is selected from In 3+ , Ga 3+ 、Zn 2+ , Cu 2+ One or more of, x1 and y1 are determined by a method of balancing the chemical formula of metal phosphide quantum dots; The general formula of the metal oxide quantum dot is M3 x2 O y2 , wherein M3 is selected from Cu 2+ 、Zn 2+ , Fe 3+ , Ba 2+ 、Ti + , Li + , Mn 3 + , Mn 4+ One or more of, x2 and y2 are determined by a method of balancing the chemical formula of metal oxide quantum dots; The general formula of the metal nitride quantum dot is M4 x3 N y3 , wherein M4 is selected from Ti 3+ 、Al 3+ , Ga 3+ , Fe 3+ , Fe 4+ One or more of, x3 and y3 are determined by a method of balancing the chemical formula of metal nitride quantum dots; The silicon-based quantum dots include one or more of intrinsic silicon-based quantum dots and doped silicon-based quantum dots; The organic quantum dots include one or more of conjugated polymer quantum dots, dendrimer quantum dots, and organic small molecular weight quantum dots; The size of the quantum dots is 3 nm to 30 nm.
4. The quantum efficiency enhancement film for solar cells according to claim 1, characterized in that: The polymer matrix includes one or more of polyvinyl alcohol, polyethylene terephthalate, polycarbonate, polyethylene-polyvinyl acetate copolymer, ethylene and octene copolymer, polyvinyl butyral, polyvinylidene fluoride, polyvinyl acetate, cellulose acetate, polysulfone, aromatic polyamide, polyimide, polystyrene, polymethyl methacrylate, thermoplastic polyolefin, and polyurethane.
5. The quantum efficiency enhancement film for solar cells according to claim 1, characterized in that: The dust-proof agent includes one or more of nano silicon dioxide and nano aluminum oxide.
6. The quantum efficiency enhancement film for solar cells according to claim 1, characterized in that: The light stabilizer includes one or more of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer and a hydroperoxide decomposer light stabilizer.
7. The quantum efficiency enhancement film for solar cells according to claim 1, characterized in that: The functional additives include one or more of organic small molecule passivators, high molecular polymer passivators, surfactants, high molecular dispersants, amino acids and their derivatives, organic phosphonic acid compounds, conductive polymer additives, and small molecule hole transport material additives.
8. The method for preparing a quantum efficiency enhancement film for solar cells according to any one of claims 1 to 7, characterized in that: The preparation method is selected from one of Scheme I to Scheme II: Option I: S1: heating the polymer matrix and coating the polymer matrix with quantum dots; S2: mixing the product obtained in S1 with a dust suppressant, a light stabilizer and a functional additive to form a quantum efficiency enhancement film for solar cells; Option II: Step 1: heating the polymer matrix and coating the polymer matrix with quantum dots; Step 2: Mixing the light stabilizer obtained in S1 and the functional additive; Step 3: Finally, apply a dust repellent to form a quantum efficiency enhancement film for solar cells.
9. The preparation method according to claim 8, characterized in that: The heating temperature is 95° C. to 105° C., and the heating time is 9 min to 11 min.
10. Use of the quantum efficiency enhancement film for solar cells according to any one of claims 1 to 7 or the quantum efficiency enhancement film for solar cells obtained by the preparation method according to any one of claims 8 to 9 in solar cells.
Citation Information
Patent Citations
Perovskite quantum dot membrane, quantum dot diffusion composite membrane and preparation method of quantum dot diffusion composite membrane
CN107955199A
Preparation method of quantum dot light conversion adhesive film capable of improving conversion efficiency of solar cell
CN116640535A
Polymer-perovskite quantum dot composite adhesive film for photovoltaic cell and preparation method of polymer-perovskite quantum dot composite adhesive film
CN117701178A
Formula of synergistic nano sol for photovoltaic panel
CN118852896A
Perovskite quantum dot / polymer composite powder material, preparation method therefor and application thereof
WO2022089617A1